Evaluation of groundwater–surface water interaction using end-member mixing analysis (EMMA) in the middle reaches of the Tama River, Tokyo, Japan - T. Suzuki; M. Tsujimura; K. Sato; H. Asakura; H. Ueno; K. Nagano (Hydrogeology Journal, 2025)
The spatial distribution of groundwater/surface-water interaction was investigated in the complex aquifer system of the middle and upper reaches of the Tama River, located in the megacity of Tokyo, Japan. Here, the Tama River and its associated groundwater system provide important water resources for the Musashino Upland in western Tokyo, where the Tama River is considered to be a losing stream based on its hydrogeological setting. To estimate the spatial distribution of groundwater recharge from the Tama River, major inorganic constituents and stable isotope compositions (δ 18 O and δ 2 H) were determined for 79 water samples collected from the river, springs, and wells. Principal component analysis and hierarchical cluster analysis revealed that some upland groundwaters exhibit isotopic and geochemical signatures consistent with the Tama River, particularly in shallow wells in close proximity to the river. End-member mixing analysis (EMMA) was performed using SiO 2 concentrations and δ 18 O as tracers to quantify the relative contribution of the Tama River, precipitation and deep groundwater to groundwater recharge in shallow aquifers. The results suggest that the Tama River’s contribution to groundwater recharge in alluvial aquifers ranges from 8 to 83%. The highest recharge contributions (41–83%) occur within 200 m of the river. In areas located several kilometers from the river, significant river water recharge contributions (24%) were observed in permeable aquifers hydraulically connected to the riverbed. Conversely, no recharge contributions were observed from the river to aquifers that are not connected to the riverbed.